2010
DOI: 10.1002/poc.1729
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of selenium and tellurium halides with propargyl alcohols. The regio‐ and stereoselectivity of addition to the triple bond

Abstract: A convenient method to incorporate selenium into an organic molecule is reported. Various aspects of the reaction of SeCl2 with propargyl alcohols, i.e., identity of reacting functionality, regiospecificity, and stereospecificity, differ from expectations based on known reactions of these alcohols with SCl2. Selenium dihalides undergo smooth 1,2‐addition to the triple bond of various propargylic alcohols resulting in the formation of the corresponding functionalized divinyl selenides in high yields and with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 62 publications
0
22
1
Order By: Relevance
“…In contrast to the above, were our findings in the reaction of selenium dihalides with homopropargyl alcohol. 16 Although some loss of stereo-and regioselectivity was observed, Z-anti-Markovnikov adducts 4 were chromatographically isolated as major products and underwent oxidation with H 2 O 2 to the corresponding fivemembered spiroselenuranes 5 with exocyclic double bonds (Scheme 3). In an alternative approach to the preparation of spirodioxaselenuranes, we have found that but-2-yn-1,4-diol smoothly reacts with selenium dihalides in a completely stereospecific manner and affords the corresponding water-soluble tetrahydroxymethyldivinyl selenides 6a,b in high yields.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the above, were our findings in the reaction of selenium dihalides with homopropargyl alcohol. 16 Although some loss of stereo-and regioselectivity was observed, Z-anti-Markovnikov adducts 4 were chromatographically isolated as major products and underwent oxidation with H 2 O 2 to the corresponding fivemembered spiroselenuranes 5 with exocyclic double bonds (Scheme 3). In an alternative approach to the preparation of spirodioxaselenuranes, we have found that but-2-yn-1,4-diol smoothly reacts with selenium dihalides in a completely stereospecific manner and affords the corresponding water-soluble tetrahydroxymethyldivinyl selenides 6a,b in high yields.…”
mentioning
confidence: 99%
“…Recently, we have found that in situ prepared selenium dichloride, readily obtained from elemental selenium and sulfuryl chloride, 14 undergoes smooth 1,2-addition to the triple bond of various propargylic alcohols resulting in the formation of symmetrical (Z,Z)-bis(1-hydroxymethyl-2-chlorovinyl) selenides 1 in high yields and in completely regio-and stereospecific manner (Scheme 1). 15,16 Of special mechanistic interest is the observed syn-addition and anti-Markovnikov orientation.…”
mentioning
confidence: 99%
“…These were separated by column chromatography on silica gel (hexane: EtOAc 4:1 as eluent). The more polar product ( R f = 0.08, yield 42 %) was identified as selenide 1 ( n = 2) by comparison with the spectral data of a known sample …”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, we have found that all aspects of the reaction of SeCl 2 with propargyl alcohols, i.e. identity of reacting functionality, regiospecifity, and stereospecifity, differ from expectations based on known reactions of these alcohols with SCl 2 (Scheme ) . SeCl 2 , prepared in situ from elemental selenium and sulfuryl chloride, reacts with propargyl alcohols via 1,2‐addition to the triple bond rather than with the ‐OH group and affords functionalized divinyl selenides 1 in high yields and in a complete regio‐ and stereospecific manner.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation